FORMATION OF THE INSTITUTE OF PARLIAMENTARISM IN THE POST-YUGOSLAV SPACE - Люба, О. О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2017)
The factors that influenced the establishment of representative and legislative authorities inYugoslavia in the early 1990s of XX century were analyzed. The main stages of the development ofparliamentarism in the post-Yugoslav space are highlighted. A brief overview of the key features ofmodern parliaments in the countries of the former Yugoslavia is given, as well as their role inlegitimizing of the existing political regimes and rooting of the democratic political culture isanalyzed.